Fiqih Muamalah dan Dinamika Perceraian: Sebuah Tinjauan Hukum Islam - Muhammad Ari Khairan; Abdul Ghanif Herlambang; Fathurrahman Fathurrahman; Almer Ragil Amri; Wismanto Wismanto (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
This research discusses the dissolution of marriage from the perspective of fiqh muamalah, focusing on the causes, processes, and impacts of divorce. Divorce, permitted in Islam as a last resort, is often triggered by incompatibility, economic factors, and family intervention. The aim of this study is to analyze the aspects of fiqh muamalah related to divorce, examine the emotional impact on children, and explore the role of counseling in preventing divorce. This research employs a qualitative approach using library research methods to examine the issues surrounding the dissolution of marriage within the framework of fiqh muamalah. The study emphasizes that a good understanding of the rights and responsibilities in marriage, along with the application of justice principles, is crucial for ensuring that the divorce process is more humane and offers new hope for all parties involved.